PRESEPSI WANITA KARIER TERHADAP KONFLIK PEKERJAAN DAN KELUARGA - Nurlaila Nurlaila; Yolanda Mohunggo (Jurnal Manajemen Sinergi, 2013)
Each employee works naturally, have a family, both parents, husband / wife or his children . On the one hand an employee must devote attention, thought and energy to the company where she worked. On the other hand, the worker / employee must give the same thing to his family. This is where there are opportunities for the different conflicts of interest. Its direction can be of two kinds, the quality of family relationships interfere with work or family demands interfere with the quality of work of employees.This research approach is qualitative descriptive case studies (case study ). Case subjects were selected based on the justification that working women are experiencing work family conflict with work in the sector characteristics formal / managerial certain working hours, can not easily leave their work at any time, the job demands a lot of time outside working hours or working hours too time-consuming so she worked hard to devote time in balance to work and family .The results found that both of them is something that is very important and complementary , the family is an integral and very important in the life of a career woman , a job is also a woman in a wheel career building in the era of globalization.Conclusion : adult economic demands the increasingly high cost of living, education and other needs of the career woman who makes an active role, with a high level of discipline, the seriousness of which is applied in the work to make progress and add to the success mainly on economic factors, environmental impacts that occur in the real family informants seen in the company of family time is less, but the positive impact that formed the equality in gender justice, application of the theory of work and family conflict by Latihfa (2008) who said that the conflict between work and family occurs when a person must carry out a multi role, namely as an employee, couple (husband and wife) and parents. For that the informants always create a culture of effective communication within the family and always strive to meet the existing role